Product Photography Assistance - Utilizing Product Photos as Online Promotional Media for Micro, Small, and Medium Enterprises (MSMEs) in the Nanggalan Hamlet, Babadan Village, Paron Sub-District, Ngawi - Nisa, Rika Khoiru; Inggrid Dwinta Mayang Maulida Salsabillah; Malika Fildzah Nur Shabirina (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
This research aims to enhance visibility, attract potential customers' attention, and expand market share through digital platforms. The introduction of this mentoring activity encompasses the creation of high-quality MSME product photos, product photography training, and editing using Canva to promote MSME products. The methods employed in executing these activities include socialization and training methods for MSME business practitioners. KKN students provide foundational training in capturing good product photos and assist in enhancing the photo outcomes through basic editing using Canva. Furthermore, evaluations and follow-ups are also conducted to ensure the success of these mentoring activities. The anticipated outcomes include an increase in MSME product sales in the Nanggalan Hamlet, Babadan Village, Paron, Ngawi, heightened community awareness regarding local MSMEs, as well as an improvement in the skills and knowledge of MSME business practitioners in marketing strategies product marketed online. Additionally, this activity can also foster better relationships between micro, small, and medium enterprise (MSME) entrepreneurs and the community, thereby creating a healthier and more productive business environment.